Penyerapan Tenaga Kerja dan Pertumbuhan Ekonomi Menuju Era Bonus Demografi di Sumatra Barat - Maryati, Sri; Handra, Hefrizal; Muslim, Irwan (Jurnal Ekonomi dan Pembangunan Indonesia, 2021)
Indonesia’s provincial population projection in 2010–2035 shows West Sumatra is one of the provinces that may not experience a demographic bonus or it could be delayed to the next period. This study aims to analyze the determinants of sectoral employment absorption and its effect on economic growth with a demometric approach. The result shows that the absorption of labor in West Sumatra is influenced by economic variables (Gross Regional Domestic Product) and demographic variables (Human Development Index). As a consequence, the productivity and the quality of human resources become important factors to achieve demographic bonus in West Sumatra.